2013
DOI: 10.1099/ijs.0.050906-0
|View full text |Cite
|
Sign up to set email alerts
|

Verrucosispora andamanensis sp. nov., isolated from a marine sponge

Abstract: An actinomycete strain, SP03-05 T , was isolated from a marine sponge sample (Xestospongia sp.) collected from Phuket Province of Thailand. The strain was aerobic, Gram-stain-positive and produced single spores at the tips of the substrate mycelium. Strain SP03-05 T contained mesodiaminopimelic acid in the peptidoglycan; whole-cell sugars were arabinose, galactose, glucose, rhamnose, ribose and xylose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…The description is as given for Verrucosispora andamanensis (Supong et al, 2013 ). The type strain is SP03-05 = BCC 45620 = NBRC 109075 = DSM 46721.…”
Section: Discussionmentioning
confidence: 99%
“…The description is as given for Verrucosispora andamanensis (Supong et al, 2013 ). The type strain is SP03-05 = BCC 45620 = NBRC 109075 = DSM 46721.…”
Section: Discussionmentioning
confidence: 99%
“…In the List of Prokaryotic names with Standing in the Nomenclature (http://www.bacterio.net), 14 novel species of 10 genera of actinomycetes from marine sponges are cited, at the time of writing, including Actinoalloteichus hymeniacidonis (Zhang et al, 2006), Actinokineospora spheciospongiae (Kämpfer et al, 2015), Marmoricola aquaticus (de Menezes et al, 2015), Micromonospora yangpuensis (Zhang et al, 2012), Mycobacterium poriferae (Padgitt & Moshier, 1987), Rubrobacter aplysinae (Kämpfer et al, 2014), Saccharopolyspora cebuensis (Pimentel-Elardo et al, 2008), Streptomyces axinellae (Pimentel-Elardo et al, 2009), Streptomyces spongiae (Khan et al, 2011), Streptomyces tateyamensis, Streptomyces marinus, Streptomyces haliclonae (Khan et al, 2010), Tsukamurella spongiae (Olson et al, 2007) and Verrucosispora andamanensis (Supong et al, 2013). Therefore, marine sponges are a good habitat for novel species of actinomycete.…”
mentioning
confidence: 99%
“…We next tried more specialized media typically used to culture organisms such as Verrucosispora spp. (39)(40)(41). Here we found that AMM and ISP-2 (Figure 1C and 1D) media were much better suited for rapid biomass accumulation, as evidenced by the 3-5 day increase in optical density for AMM, and for ISP-2 after the 6-day time point.…”
Section: Cultivation and Domestication Of A Novel Isolate Of The Verrucosispora Genusmentioning
confidence: 50%